2019
DOI: 10.1002/hep.30541
|View full text |Cite
|
Sign up to set email alerts
|

Glial Cell Line–Derived Neurotrophic Factor Enhances Autophagic Flux in Mouse and Rat Hepatocytes and Protects Against Palmitate Lipotoxicity

Abstract: Glial cell line–derived neurotrophic factor (GDNF) is a protein that is required for the development and survival of enteric, sympathetic, and catecholaminergic neurons. We previously reported that GDNF is protective against high fat diet (HFD)‐induced hepatic steatosis in mice through suppression of hepatic expression of peroxisome proliferator activated receptor‐γ and genes encoding enzymes involved in de novo lipogenesis. We also reported that transgenic overexpression of GDNF in mice prevented the HFD‐indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…As compared to HFD-fed WT mice, GDNF transgenic mice displayed reduced expression of autophagic marker p62/sequestosome-1 and increased expression of autophagy related 5 (Atg5), Beclin 1 and microtubule-associated protein-1 light chain 3 (20). This in vivo effect of GDNF was further confirmed by in vitro analysis of autophagic flux in primary mouse hepatocytes and secondary rat cell line (74).…”
Section: Glial Cell-line Derived Neurotrophic Factor and Non-alcoholimentioning
confidence: 75%
See 1 more Smart Citation
“…As compared to HFD-fed WT mice, GDNF transgenic mice displayed reduced expression of autophagic marker p62/sequestosome-1 and increased expression of autophagy related 5 (Atg5), Beclin 1 and microtubule-associated protein-1 light chain 3 (20). This in vivo effect of GDNF was further confirmed by in vitro analysis of autophagic flux in primary mouse hepatocytes and secondary rat cell line (74).…”
Section: Glial Cell-line Derived Neurotrophic Factor and Non-alcoholimentioning
confidence: 75%
“…Autophagy maintains insulin sensitivity, regulates lipid stores, and protects against the development of inflammation (4). Work in our lab has demonstrated a stimulatory effect of GDNF on hepatic macroautophagy (20,74). As compared to HFD-fed WT mice, GDNF transgenic mice displayed reduced expression of autophagic marker p62/sequestosome-1 and increased expression of autophagy related 5 (Atg5), Beclin 1 and microtubule-associated protein-1 light chain 3 (20).…”
Section: Glial Cell-line Derived Neurotrophic Factor and Non-alcoholimentioning
confidence: 97%
“…It was recently reported that GDNF is protective in HFD-induced insulin resistance, hyperlipidemia and obesity in mice. 32, 33 In their experiments, Mwangi et al used transgenic GDNF expression in mice, and investigated GDNF responses of hepatocytes in experimental NAFLD. They convincingly showed that in the setting of hepatocyte steatosis, GDNF is protective through the downregulation of peroxisome proliferator-activated receptor- γ (PPAR-γ) expression.…”
Section: Discussionmentioning
confidence: 99%
“…To date, many studies showed defects in autophagy processes in NAFLD pathogenesis, in particular, in the early and intermediate steps of autophagy (i.e., autophagosome formation and autophagosome−lysosome fusion), which are under the control of mTOR and of TFEB. ( 2 , 7 , 8 , 35 , 36 , 37 ) We observed that RORα also functions to regulate autophagosome formation, as the number of autophagosome puncta was decreased in the hepatocytes of RORα‐LKO mice (Fig. 3D ).…”
Section: Discussionmentioning
confidence: 86%
“…(5,6) In experimental animals, the enhancement of the autophagic flux protected against palmitate lipotoxicity in murine hepatocytes. (7) In addition, liver injury and inflammation were increased when hepatic autophagy was reduced by genetic knockout of autophagy-related 5 in a mouse model. (8) The degradative ability of the autophagic pathway is afforded by lysosomes.…”
mentioning
confidence: 99%